Aktivitas Antibakteri Ekstrak Metanol Biji Buah Xylocarpus granatum Terhadap Isolat Bakteri Ikan Nila (Oreochromis niloticus): Antibacterial Activity of Methanol Extract of Xylovcarpus granatum Fruit Seeds Against Tilapia (Oreochromis niloticus) Bacterial Isolates (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2024)
The use of various types of mangroves is effectively used as a natural ingredient in inhibiting the growth of bacteria in fish. Fruit of Xylocarpus granatum contains secondary metabolites that have the potential as natural antibacterials. This study aims to determine the antibacterial activity and determine the value of the Minimum inhibitory concentration (MIC) of the methanol extract of X. granatum fruit seeds. The research stages consisted of seed preparation and extraction of X. granatum, isolation of bacteria from tilapia gills, inhibition testing, MIC testing, and Total Plate Count (TPC) testing. Preparation was done by thinly slicing the seeds of X. granatum and air-wdrying for 30 days. The dried seeds (simplicia) were reduced in size using a blender and then extracted by maceration using 98% methanol solvent for 24 hours, then filtered. The filtrate was separated from the methanol solvent using a rotary evaporator at a temperature of 600 °C to obtain the extract of X. granatum seeds. The content of secondary metabolites of the methanol extract of X. granatum seeds was found to be alkaloids, triterpenoids, flavonoids, saponins, phenols, and tannins. The treatment in this study were used methanol extract of X. granatum seeds with 3 concentrations (100 ppm, 500 ppm, 1000 ppm) and positive control (Chloramphenicol) 1000 ppm and negative control (sterile distilled water). The parameters observed were the inhibitory activity, the MIC, and the TPC. The results showed that the methanol extract of X. granatum fruit seeds had the ability to inhibit the growth of bacteria isolated from the gills of tilapia fish with moderate categories (9-9.8 mm) at concentrations of 100 ppm and 500 ppm and the concentrations of 1000 ppm with strong categories (11.5 mm) at 48 hours. The MIC of X. granatum seed methanolic extract on isolates of tilapia gill bacteria was at a concentration of 40 ppm. The results of the TPC test at a concentration of 40 ppm were 5.5×107 CFU/ml, with inhibition activity against 91.67% of bacterial growth.